Structural, optical and thermal properties of Sm₂O₃/Bi₂O₃-doped zinc silicate glass ceramics from rice husk ash - AbuBakar, Auwalu Inusa (2017)
The solid waste disposal has become a persistence problem in our communities. This evolves due to our rapid increase in population that leads to the growth of our industrial and agricultural sectors. A dramatic increase of solid waste deposition is experienced. Virtually, different collection of items is disposed, which change the compositional statues of our environments. Formally, solid waste disposal was carried out by incinerators technique. However, the burning of solid waste materials pollutes the surroundings. The community screams against the hazardous air pollution from incineration of waste materials. Hence, the technique changes to landfills solid waste disposal. Besides, this process tremendous number of problems is encompassing it, which changes the scientists and researchers way of thinking to the conversion of waste materials. Therefore, a subset of agricultural waste known as waste rice husk is converted to a useful material, known as white rice husk ash (WRHA) is used in carrying out this experimental work for this thesis. Conventional melt quenching technique was used to synthesis and characterize Sm3+/Bi3+ doped zinc silicate derived from WRHA for the structural, optical and thermal properties. Some of the major findings were given as followed. At high sintering temperature, Porosities were decreased due to the diffusion of the ions into based precursor. The poly grains turned to aggregate with one another with increasing doping concentrations. The phonon was responsible for the conveying the heat energy. An increasing heat movement was noticed with growing samarium dopant concentrations. However, a fluctuated heat movement was observed due to the oxidation and de oxidation of Bi3+ ions. The decrement energy band gaps of the samples were occurring because of the conversion of bridging oxygen to non-bridging oxygen. Hence, in conclusion Samarium/Bismuth oxides doped zinc silicates were successfully synthesized via melt quenching technique. Porosity decreases with increase of Sm3+ / Bi3+ ions concentrations. The poly grains increase in size with increasing of Sm3+ / Bi3+ ions concentrations. The sample agglomerated more with 5 wt% increment of Sm3+ / Bi3+ ions concentrations. Thermal diffusivity increases with increase of samarium concentrations. Thermal diffusivity fluctuates with increase of bismuth concentrations. Optical band gap of bismuth doped zinc silicate decreases with increase of bismuth concentrations. Optical band gap of samarium doped zinc silicate increases at 3 wt% and decreases with 5 wt% samarium concentrations. Refractive index decreases with Sm 3 wt% and increases with Sm 5 wt% while molar refraction and polarizability increase with samarium concentrations up to 3 wt% and decrease to 5wt%. Refractive index, molar refraction and polarizability decrease with increasing of bismuth concentrations. Finally, the outcomes of XRD, FESEM, and FTIR transmittance spectra showed the formation of zinc silicate phase in the precursor ZnO-WRHA glass ceramics. The FESEM micrograms indicated the formation of well-defined zinc silicate phase with highly agglomerated Samarium/Bismuth oxides -doped zinc silicate glass ceramics. The crystallite size acquired from XRD pattern differs in the range of 54-59 nm for samarium oxides -doped zinc silicate and 41-94 nm for bismuth oxides -doped zinc silicate. The presence of Zn-O and Si-O-Zn vibration bands in Infrared spectra shows the features of willemite phase formation. The UV-Visible analysis displays the value of optical band gap, which reduces with growing in doping concentrations, and the sintering temperature improves the willemite crystallinity in the precursor ZnO-WRHA glass ceramics. Furthermore, the luminescence spectra of glass-ceramics establish that the Sm3+/ Bi3+ ions are diffusing into the glass-ceramic phase and through that improved the photoluminescence of the doped willemite glass-ceramics. Hence, the emission intensity of Zn2SiO4:Sm3+ phase showed red luminescence focused at 646.71 nm whereas the emission fixed at 621.57 nm developed from Zn2SiO4:Bi3+ phase matches to the 4G5/2–6H7/2 transition. The thermal diffusivities values grow with dopants proportions with the least value of 0.2039 - 0.1392 mm2/s and highest value of 0.4375–0.2653 mm2/s for Zn2SiO4:Sm3+. Again, the thermal diffusivities values fluctuate with dopant concentrations with the least value of 0.2008–0.1383 mm2/s and the highest value of 0.2329-0.1570 mm2/s for Zn2SiO4:Bi3+. For that reason, Zn2SiO4:Sm3+ glass-ceramics seems to be favorable for use in solid-state lasers as a promising phosphor material. On the other hand, Zn2SiO4:Bi3+ glass-ceramics suggests being favorable for use on radar screen as a promising phosphor material.